2012
DOI: 10.3390/molecules171213769
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng Marc Oil Inhibits iNOS and COX-2 via NFκB and p38 Pathways in LPS-Stimulated RAW 264.7 Macrophages

Abstract: In this study, we investigated the anti-inflammatory effects of red ginseng marc oil (RMO) in the RAW 264.7 macrophage cell line. RMO was prepared by a supercritical CO2 extraction of waste product generated after hot water extraction of red ginseng. RMO significantly inhibited the production of oxidative stress molecules such as nitric oxide and reactive oxygen species in lipopolysaccharide (LPS)-activated RAW 264.7 cells. Levels of inflammatory targets including prostaglandin E2, tumor necrosis factor-α, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 57 publications
3
68
0
1
Order By: Relevance
“…Flavonoids, sterols, and triterpenoids compounds have anti-inflammatory activity by inhibiting the 5-lipoxygenase pathway, which together with the COX-2 pathway, is very important in producing and maintaining inflammation. This previously has been shown(Suh et al, 1998;Mosquera et al, 2011;Bak et al, 2012).…”
supporting
confidence: 62%
“…Flavonoids, sterols, and triterpenoids compounds have anti-inflammatory activity by inhibiting the 5-lipoxygenase pathway, which together with the COX-2 pathway, is very important in producing and maintaining inflammation. This previously has been shown(Suh et al, 1998;Mosquera et al, 2011;Bak et al, 2012).…”
supporting
confidence: 62%
“…Girinimbine was shown to have considerable antioxidant activity. Phytochemicals have been reported to suppress iNOS and COX-2 promoter activities and inhibit NF-κB nuclear translocation in LPS-treated cells 64. Pyrano [3,2-a] carbazoles such as girinimbine, isolated from plant species of the Rutaceae family, were reported to possess these anti-inflammatory and antioxidant activities 65.…”
Section: Discussionmentioning
confidence: 99%
“…has been revealed to promote HG [52][53][54]. Treatment of mice with RGO upregulates Wnt/β-catenin and Shh/Gli-pathways-mediated expression of genes such as β-catenin, Lef-1, sonic hedgehog, Cyclin D1, and Cyclin E [55]. In addition, RGO and its major components downregulate TGF-β [56][57][58] and enhance antiapoptotic protein Bcl-2 expression [55].…”
Section: Panax Ginseng Ca Meymentioning
confidence: 99%
“…Treatment of mice with RGO upregulates Wnt/β-catenin and Shh/Gli-pathways-mediated expression of genes such as β-catenin, Lef-1, sonic hedgehog, Cyclin D1, and Cyclin E [55]. In addition, RGO and its major components downregulate TGF-β [56][57][58] and enhance antiapoptotic protein Bcl-2 expression [55]. Matsuda H. et al, (2003) reported the promotion of HG by ginseng radix on cultured mouse vibrissal HF [59].…”
Section: Panax Ginseng Ca Meymentioning
confidence: 99%